PENINGKATAN KETERAMPILAN HIDUP DASAR MELALUI PROGRAM SEKOLAH SEHAT DI SDN 2 PETUK KATIMPUN KOTA PALANGKA RAYA - Uswatun Hasanah Purnama Sari; Zuly Daima Ulfa Ulfa; Muhammad Irmawan Irmawan; Tiara Lestari; Meiman Syukur Halawa; Diah Panjar Arum; Ikhtiar Zendarto (BULETIN ILMIAH NAGARI MEMBANGUN, 2025)
Basic life skills serve as a fundamental pillar in shaping students' character to become healthy, independent, and empowered from an early age. This programme aimed to enhance students’ basic life skills through the implementation of the Healthy School Programme at SDN 2 Petuk Katimpun, Palangka Raya. Activities were conducted over a three-month period, from August to October 2024, encompassing the following stages: problem identification, socialisation, focus group discussions, training, mentoring, and evaluation. The interventions included the formation of peer support groups, education on balanced nutrition, life skills training, waste management based on the 3R principles (reduce, reuse, recycle), and the organisation of the Healthy and Creative Children’s Festival. The results indicated a significant improvement in students' knowledge scores (from 65.1 to 73.6) and attitudes (from 55.2 to 70.4) regarding healthy behaviours. The establishment of peer groups as educators proved effective in supporting behavioural changes, particularly in promoting healthy packed meals and waste sorting. Educational activities such as the nutrition-themed snakes and ladders game and crafts made from plastic waste successfully increased students’ engagement in an enjoyable and participatory manner. In conclusion, an educational and participatory approach grounded in life skills development was found to be effective in supporting the implementation of a healthy school environment. Sustainability of the programme is recommended through cross-sectoral collaboration and the development of replicable educational media. This model may serve as a reference for similar initiatives in other schools, particularly in areas facing environmental and behavioural challenges.